2017
DOI: 10.1371/journal.pone.0174461
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of mRNA, microRNA alteration and aberrant DNA methylation patterns in rectal adenocarcinoma

Abstract: AimRectal adenocarcinoma (READ) is a malignancy cancer with the high morbidity and motility worldwide. Our study aimed to explore the potential pathogenesis of READ through integrated analysis of gene expression profiling and DNA methylation data.MethodsThe miRNA, mRNA expression profiling and corresponding DNA methylation data were downloaded from The Cancer Genome Atlas (TCGA) database. Differentially expressed mRNAs/ miRNAs/methylated regions (DEmRNA/DEmiRNAs) were identified in READ. The negatively correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
(42 reference statements)
2
18
1
Order By: Relevance
“…DNA methylation is crucial for mammalian embryo development which is dynamically regulated by the action of the DNA methyltransferases (DNMTs) and ten eleven translocation enzymes (TETs) (Ambrosi, Manzo, & Baubec, ; Li & Zhang, ; Lim, Knowles, Solter, & Messerschmidt, ). As both targets and effectors of DNMTs and TETs, miRNAs play pivotal roles in regulating DNA methylation (Hua et al., ; Jin, Li, Ouyang, Tan, & Jiang, ; Shivakumar et al., ). DNA methylation can inhibit the transcription of miRNAs by methylating the CpG islands in the promoter regions of miRNAs, and certain miRNAs can directly target DNA methylation‐related enzymes, thereby affecting the whole genome methylation pattern (Chhabra, ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is crucial for mammalian embryo development which is dynamically regulated by the action of the DNA methyltransferases (DNMTs) and ten eleven translocation enzymes (TETs) (Ambrosi, Manzo, & Baubec, ; Li & Zhang, ; Lim, Knowles, Solter, & Messerschmidt, ). As both targets and effectors of DNMTs and TETs, miRNAs play pivotal roles in regulating DNA methylation (Hua et al., ; Jin, Li, Ouyang, Tan, & Jiang, ; Shivakumar et al., ). DNA methylation can inhibit the transcription of miRNAs by methylating the CpG islands in the promoter regions of miRNAs, and certain miRNAs can directly target DNA methylation‐related enzymes, thereby affecting the whole genome methylation pattern (Chhabra, ).…”
Section: Introductionmentioning
confidence: 99%
“…HAND2 is a basic helix-loop-helix transcription factor that plays a very important role in the development and differentiation of the heart and nervous system [ 26 ]. Recent studies revealed that HAND2 was significantly hypermethylated and downregulated in colon and rectal cancer [ 27 , 28 ]. In addition, continuous proliferation of the endometrium was observed in mice with knockdown of HAND2 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that other mechanisms are also involved in colorectal cancer. Hua et al (2017) used TCGA database to explore mRNA expression profiling and corresponding DNA methylation data. Eventually, 50 differentially expressed (DE) mRNAs DEmRNAs (39 down- and 11 upregulated DEmRNAs) with hypermethylation, synchronously negatively targeted by DEmiR, were identified through the correlation analysis among 446 genes with aberrant methylation and 668 miR, evidenced from rectal adenocarcinoma tumor samples.…”
Section: Mechanisms Of Mir In Colorectal Cancermentioning
confidence: 99%
“…Eventually, 50 differentially expressed (DE) mRNAs DEmRNAs (39 down- and 11 upregulated DEmRNAs) with hypermethylation, synchronously negatively targeted by DEmiR, were identified through the correlation analysis among 446 genes with aberrant methylation and 668 miR, evidenced from rectal adenocarcinoma tumor samples. They further used qRT-PCR and microarray analyses to validate and identified 7 genes of SORCS1, PDZRN4, LONRF2, CNGA3, HAND2, RSPO2, and GNAO1 with hypermethylation and negatively regulation by DEmiR, the seven of which might contribute to the tumorigenesis of rectal adenocarcinoma ( Hua et al, 2017 ). Stable expression of SNAI1 in DLD1 and HCT116 cells downregulates miR-145 expression compared to control cells.…”
Section: Mechanisms Of Mir In Colorectal Cancermentioning
confidence: 99%